Impact of the cannabis cultivation on the physico-chemical degradation and hydrodynamic behaviour of soils in the wadi Sra Catchment, (Central Rif, Morocco) - El-Ommal, Mouhssine; Tribak, Abdellatif; Amhani, Zakariae; Arari, Khalid (Revista de Estudios Andaluces, 2024)
The Oued Sra basin is part of the Central Rif in northern Morocco; It constitutes a fragile environment where soil degradation is spectacular. The objective of the present work is to study the impacts of cannabis cultivation on the physicochemical properties of soils, their surface characteristics, as well as their hydrodynamic behaviors during different seasons. The study is based on analyzes of the physicochemical properties of the surface horizons of the soil (0-25 cm), based on the choice of control plots under forest and other plots cleared and put into cannabis cultivation for 10 yrs. The surface condition of the plots concerned was verified in the field, using the quadrat point method. The hydrodynamic behavior of the soil and detachability were measured using a mini-ramp rain simulator on micro-plots (1m2). The obtained results show that the soils reach very advanced levels of degradation; marked by a significant reduction in fertility and a predominance of bare (90%) and closed (71%) surface states on cleared land used for cannabis cultivation. On these lands, cleared for at least ten years, fertilizers inputs are mainly chemical fertilizers applied intensively. The rotations practiced are twice a year, due to the scarcity of available agricultural land, population growth and the financial gain brought by cannabis cultivation. Likewise, the simulation tests result in maximum final infiltration values ​​recorded on cereal growing land (67.20 mm/h); while land intended for cannabis cultivation recorded low values ​​(43.12 mm/h). Consequently, the maximum averages of solid transport are recorded in the cannabis growing lands (98.87 g/l) but the cereal growing lands are marked by low values ​​(26.64 g/l).